(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Financing mechanisms of enterprises are of particular importance in the organization of cluster production based on socio-economic reforms implemented in the region. Because, if the principles of financial management and the mechanisms of its implementation are correctly applied in enterprises operating on the basis of a cluster, it will lead to the correct and efficient use of the financial resources of the enterprise, and this will affect the management efficiency of the enterprise. From this point of view, in this article, the financing mechanisms of enterprises operating on the basis of the cluster system, as well as the reduction of the state’s role in agricultural production, the use of tax incentives for the purpose of promotion, the state of organization of financial management in such enterprises in Uzbekistan related issues are highlighted, problems are identified and some recommendations are given.